A previously unappreciated polymorphism in the beta chain of I-As expressed in autoimmunity-prone SJL mice: Combined impact on antibody, CD4 T cell recognition and MHC class II dimer structural stability. (March 2022) - Richards, Katherine A.; Lavery, Courtney; Keller, Grant L.J.; Miller, Jim; Baker, Brian M.; Sant, Andrea J.
Highlights: A rare and unreported mutation was discovered in I-A s expressed autoimmunity prone SJL mice. A single amino acid polymorphism alters MHC class II structural features. CD4 T cell reactivity with I-A s suggests TcR docking towards peptides' amino terminus. Autoimmune T cells may share common features of T cell receptor recognition. Abstract: In the process of structure-function studies on the MHC class II molecule expressed in autoimmunity prone SJL mice, I-A s, we discovered a disparity from the reported sequence of the MHC class II beta chain. The variant is localized at a highly conserved site of the beta chain, at residue 58. Our studies revealed that this single amino acid substitution of Pro for Ala at this residue, found in I-A s, changes the structure of the MHC class II molecule, as evidenced by a loss of recognition by two monoclonal antibodies, and elements of MHC class II conformational stability identified through molecular dynamics simulation. Two other rare polymorphisms in I-A s involved in hydrogen bonding potential between the alpha chain and the peptide main chain are located at the same end of the MHC class II binding pocket, studied in parallel may impact the consequences of the β chain variant. Despite striking changes in MHC class II structure, CD4 T cell recognition of influenza-derived peptides was preserved. These disparate findings were reconciled by discovering, through monoclonal antibody blocking approaches, that CD4 T cell recognition by I-A s restricted CD4 T cells focused more on the region of MHC class II at the peptide's amino terminus. These studies argue that the conformational variability or flexibility of the MHC class II molecule in that region of I-A s select a CD4 T cell repertoire that deviates from the prototypical docking mode onto MHC class II peptide complexes. Overall, our results are consistent with the view that naturally occurring MHC class II molecules can possess polymorphisms that destabilize prototypical features of the MHC class II molecule but that can maintain T cell recognition of the MHC class II:peptide ligand via alternate docking modes.